Current management of renal cell cancer. Issue 2 (March 2017) - Spain, Lavinia; Turajlic, Samra
Abstract : The last decade has seen significant treatment advances in the management of renal cell cancer, from the availability of oral, targeted therapies to the recent introduction of immunotherapy. In this article the authors cover the risk factors for renal cancer and its different histological types, as well as the staging and management of both early and late‐stage disease.